Potent Tyrosinase Inhibitory Activity of Curcuminoid Analogues and Inhibition Kinetics Studies - Anan Athipornchai; Nattisa Niyomtham; Wachirachai Pabuprapap; Vachiraporn Ajavakom; Maria Duca; Stéphane Azoulay; Apichart Suksamrarn (Cosmetics, 2021)
Natural tyrosinase inhibitors from herbal plants are promising therapeutic agents for skincare and cosmetic products. Natural curcuminoids exhibit weak antityrosinase properties. The structural modification of curcumin, the major curcuminoid from Curcuma longa, gave 14 analogues. The tyrosinase inhibitory activity of the natural curcuminoids and the modified analogues on both L-tyrosine and DOPA substrates were evaluated. The inhibition kinetics were also undertaken. For analogues with potent activity on the L-tyrosine substrate, the isoxazole analogue 12 and two reduced analogues, hexahydrocurcumin (16) and the α,β-unsaturated analogue 17, showed IC50 values of 8.3, 14.6 and 9.4 µM, and were 20.9-, 11.9- and 18.4-fold more active, respectively, than kojic acid, the reference compound. For the analogues with potent antityrosinase on DOPA substrate, the dimethylated analogue 5 exhibited the strongest antityrosinase activity against the DOPA substrate, with the IC50 value of 8.0 µM, which was 16.6-fold more active than kojic acid. The inhibition kinetics revealed that curcuminoid 5 could bind with both free enzyme and with the enzyme–substrate complex. It acted as a competitive–uncompetitive mixed-II type inhibitor. Curcuminoid 17 could bind with both free enzyme and the enzyme–substrate complex. The results indicated that 17 acted as a competitive–uncompetitive mixed-I type inhibitor, while curcuminoid 12 was a noncompetitive inhibitor which bound with both free enzymes and the enzyme–substrate complex. These potent analogues might serve as new potential tyrosinase inhibitors for the prevention and treatment of skin pigmentation disorders.